ANALISIS TEKANAN UDARA PADA PROSES THERMAL SPRAY ALUMINIUM TERHADAP KEKUATAN ADHESI DAN KETEBALAN LAPISAN COATING PADA BAJA AISI 1020 - Fillah, Moh. Yusron; Hastuti, Sri; Nurhadi; Darmo, Adityo Noor Setyo Hadi (POLITALA PRESS, 2025)
The thermal spray aluminum (TSA) coating method is used to prevent damage to the metal surface and improve the quality of the metal surface by bonding the coating. The coating standard has a minimum thickness of 80-100 µm. According to AWS C2.23M/C2.23, NACE N0.12, SSPC CS-23, coatings submerged in seawater will experience a decrease in coating thickness of 20 µm. This study aims to examine the effect of air pressure in the thermal spray coating process on AISI 1020 steel on the bond strength of the coating to the base metal. The research was conducted using air pressure variations of 3 Bar, 3.5 Bar, and 4 Bar. Furthermore, dry film thickness, pull off adhesive, and bending tests were conducted. The dry film thickness test results show that the higher the air pressure, the coating thickness increases. The results of the pull off adhesive test show that the higher the air pressure the bonding strength of the coating also increases. The bending test results show results that are in accordance with standard practice item No.21100 where there are no cracks and small cracks are still allowed.